Photo-induced DNA cleavage by zinc-substituted myoglobin with a redesigned active center. Issue 12 (30th October 2017) - Shi, Zhen-Hua; Du, Ke-Jie; He, Bo; Gao, Shu-Qin; Wen, Ge-Bo; Lin, Ying-Wu
Abstract : Artificial nucleases were constructed by the redesign of the heme center in myoglobin (Mb) and replacement of the native heme with zinc protoporphyrin (ZnPP), which exhibit tunable photo-induced DNA cleavage activity. Abstract : Myoglobin with a redesigned active center was constructed and reconstituted with zinc protoporphyrin (ZnPP), which was shown to exhibit novel photo-induced DNA cleavage activities, involving a hydroxyl radical (˙OH) with a minor contribution from singlet oxygen ( 1 O2 ), as confirmed by spin-trapping studies for the first time.